Sometimes the Snitch Recants: A Closer Look at the Use of Jailhouse Informants in DNA Exoneration Cases - Heath, Wendy Pamela; Stein, Joshua Robert; Singh, Sneha; Holden, Da'Naia Lynnette (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2023)
The purpose of this study is to investigate further the role of jailhouse informants in U.S. DNA exoneration cases. Thus, for the first 375 DNA exoneration cases compiled by the Innocence Project (“IP”), we reviewed the IP information relevant to jailhouse informant testimony. We supplemented the information from the IP with that from the National Registry of Exonerations (“NRE”) and the Convicting the Innocent (“CTI”) databases.We found that 15% of these DNA exoneration cases included jailhouse informant testimony, with White people more likely than Black people to have an informant involved in their case. There was also a greater tendency for defendants incriminated by informants to be given the death penalty. In 13% of the cases, the only evidence supporting a conviction was the word of the jailhouse informant. We also found that in 24% of cases which had at least one jailhouse informant, the informant recanted. This has thus led to an effort in some jurisdictions for reform regardinginformant testimony. While states should continue to consider adopting procedures to curb the reliance on unreliable informants, we recommend that any reform regarding the use of informants should include a consideration of recanting informants.